Analisis Yuridis Penyelesaian Perkara PT. Sarana Farmindo Utama (Putusan Perkara Nomor: 28/KPPU-M/2019) - Eqlima Dianti Agustianingrum; Diniati Wafida Rohmah (Jurnal Hukum dan Sosial Politik, 2024)
Basically, merger, merger, and expropriation are actions that are unknown and also not developed in Indonesia. Mergers, mergers, and takeovers are also very vulnerable to monopolistic practices and unfair business competition, therefore the Law on antimonopoly strongly violates marger, acquisition, and consolidation which is likely to result in monopolistic practices or unfair business competition, which has been regulated in Article 29 of Law Number 5 of 1999 concerning the Prohibition of Monopoly Practices and Unfair Business Competition. The Competition Supervisory Commission also has the obligation to conduct investigations and examinations on unfair business actors, and the existence of unfair business competition can result in an imbalance of economic power because it is controlled by one pillar only and this can lead to unfair business competition. The purpose of this study is to be able to understand the takeover procedure carried out by PT. Sarana Farmindo Utama to PT. The prospect of Karyatama in Decision Number Case 28 / KPPU-M / 2019 and also to be able to understand the settlement of cases carried out by PT. Sarana Farmindo Utama in the case of the takeover of shares of PT. Karyatama Prospects. Based on the results of the share takeover research conducted by PT. Sarana Farmindo Utama is to save PT. The prospect of Karyatama almost going bankrupt and also to continue to run as a feeder for livestock chickens, a violation that was carried out by PT. Sarana Farmindo Utama is late notification of takeover to the Commission. And PT. Sarana Farmindo has been legally penalized by paying fines, and is also required to submit proof of fine payments to the Business Competition Supervisory Commission.